2021
DOI: 10.3390/ijms22041892
|View full text |Cite
|
Sign up to set email alerts
|

Plant HKT Channels: An Updated View on Structure, Function and Gene Regulation

Abstract: HKT channels are a plant protein family involved in sodium (Na+) and potassium (K+) uptake and Na+-K+ homeostasis. Some HKTs underlie salt tolerance responses in plants, while others provide a mechanism to cope with short-term K+ shortage by allowing increased Na+ uptake under K+ starvation conditions. HKT channels present a functionally versatile family divided into two classes, mainly based on a sequence polymorphism found in the sequences underlying the selectivity filter of the first pore loop. Physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 85 publications
1
33
0
Order By: Relevance
“…In plants, there are two classes of HKTs (HKT1-like and HKT 2-like). Class I HKTs are Na + uniporters and class II HKTs are Na + and K + symporters [ 14 ]. The KEA proteins are closely related to bacterial KefC K + /H + antiporters [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, there are two classes of HKTs (HKT1-like and HKT 2-like). Class I HKTs are Na + uniporters and class II HKTs are Na + and K + symporters [ 14 ]. The KEA proteins are closely related to bacterial KefC K + /H + antiporters [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we also noted that a maximum number of HKT proteins that consisted of five or less motifs were found in subfamily V. The results further noted that the physicochemical properties of all HKT proteins were similar in each subfamily. These results suggest that HKT proteins shared a close evolutionary relationship during biological evolution in plants [ 45 , 46 ]. The intron–exon distribution revealed that most HKT genes possessed two exons and one intron ( Figure 2 ), further confirming that the HKT genes may have close evolutionary relationships in plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This transporter could transport Na + out of the xylem, and transport Na + from the phloem back to the root where it was excreted from the plant through the action of other Na + transporters. This process reduced the Na + content in the shoot, regulated the Na + /K + balance in the shoots, and improved rice salt tolerance [ 68 ].…”
Section: Qtl Analysis Of Salt Tolerance In Ricementioning
confidence: 99%